Transformasi Digital Dalam Pemasaran Layanan Kesehatan: Dampaknya Terhadap Perilaku Konsumen (Systematic Literature Review) - Ronald Reidi Kambey; Vinnie Widayanti; Kurnia Popy Rakhmawati (Integrative Perspectives of Social and Science Journal, 2026)
marketing paradigms. The objective of this research is to analyze the impact of digital transformation on consumer behavior and to identify key influencing factors. The study employs a systematic literature review approach following PRISMA guidelines to ensure transparency and methodological rigor. Data were collected from reputable scientific databases using strict inclusion criteria focusing on relevant empirical studies. The findings indicate that digital marketing consistently enhances patient visit intention, satisfaction, and loyalty through improved brand awareness and user experience. Interactivity, personalization, and content quality emerge as key determinants influencing consumer decision-making. Furthermore, the integration of technologies such as business intelligence and social media strengthens the effectiveness of healthcare marketing strategies. In conclusion, digital transformation serves as a strategic determinant in shaping consumer behavior and enhancing the competitiveness of healthcare services in the modern era.